Anatomy of smooth muscle cells in nonmalignant and malignant human prostate tissue - Taboga, Sebastiao R. [UNESP]; Scortegagna, Eduardo; Siviero, Maristela P.; Carvalho, Hernandes F. (Wiley-liss, 2008)
Differently graded areas of human prostate adenocarcinoma were examined after Masson's trichrome staining or immunohistochemistry for smooth muscle alpha-actin, type IV collagen and laminin. In addition, the ultrastructure of the prostatic smooth muscle cells (SMC) during glandular proliferation and epithelial invasion in selected tumors was studied. The SMC formed a thick layer below the epithelial structures in unaffected areas and were closely associated with each other in homotypic interactions. As the tumor grade increased, the SMC gradually lost interactions with each other and became atrophic. With the growth of the epithelial compartment, the SMC initially segregated to the tumor periphery and the intercellular spaces increased. In high grade tumors, the epithelial cancer cells invaded the spaces between the SMC. Immunohistochemical analysis of the basal membrane revealed increased disruption of the usually thick basal membrane, which became thinner and faintly stained with each of the antibodies used. We conclude that most SMC become atrophic following epithelial invasion in human tumors and that degradation of the basal membrane is an important factor in this process. At the ultrastructural level, different SMC phenotypes occur in prostatic tissues during epithelial invasion. Interconversion between these phenotypes is suggested and a probable relationship among them is proposed.
Keywords: tumor invasion; prostatic cancer; Smooth muscle cells; prostate cancer